China : Does Government Health and Education Spending Boost Consumption? - Barnett, Steven; Brooks, Ray. (Washington, D.C. : International Monetary Fund, 2010)
Consumption in China is unusually low and has continued to decline as a share of GDP over the past decade. A key policy question is how to reverse this trend, and rebalance growth away from reliance on exports and investment and toward consumption. This paper investigates whether the sizable increase in government social spending in recent years lowered precautionary saving and increased consumption. The main findings are that spending on health, but not education, had an impact on household behavior. The impact, moreover, is large. A one yuan increase in government health spending is associated with a two yuan increase in urban household consumption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet